O impacto econômico do futebol no cenário global: um estudo sobre a FIFA de 1990 a 2018 - Cazotto, Gabriel Nickolas (2018)
This thesis has as main objective to study the economic impact of football in the international scenario, mainly through the World Cup. This research focuses on the economic and political acting of FIFA, since its origins to the present. The study covers its juridical legality, its performance in the context of international governance and the financial movement that football brings within various sectors of the world economy. Finishing with the impact that the organization of the World Cup causes as much on the infrastructure, tourist movement and marginal growth of the GDP in the last two host countries, South Africa and Brazil, as the expectations for Russia tournament. The study also observes the question of FIFA's earning of revenue over the last fifteen years and how the rules of affiliation of new countries are influenced by nationalism and the geopolitical consequences of joining FIFA.